TRAINING PROTOCOL ON CHANGES IN BLOOD GLUCOSE LEVELS AND BLOOD PRESSURE IN TYPE 1 DIABETES PATIENTS (CIPEEX, 2025)
Type 1 Diabetes Mellitus (T1DM) is an endocrine condition resulting from the autoimmune destruction of pancreatic beta cells, leading to severe insulin deficiency. Clinically, T1DM manifests with symptoms such as polyuria, polydipsia, xerostomia, unexplained weight loss, fatigue, polyphagia, and blurred vision. Glycemic self-monitoring is a critical process for these patients, allowing the measurement of glucose in different contexts such as home, school, and work environments, and adjusting the insulin dose as needed. According to data from the International Diabetes Federation, in 2019, Brazil ranked fifth globally in terms of diabetes prevalence, with 16.8 million adults affected in the age group of 20 to 79 years. The American Diabetes Association recommends that adults with T1D engage in at least 150 minutes per week of moderate to vigorous physical activities. For children and adolescents with T1D, it is recommended to engage in at least 60 minutes of daily physical activity, including muscle and bone strengthening exercises three times a week. Regular physical activity is associated with a reduced risk of future cardiovascular diseases, improved long-term glycemic control, better cardiovascular conditioning, quality of life, reduced daily insulin needs, and better weight control. Moreover, it plays a crucial role in the primary and secondary prevention of diabetes-related cardiovascular diseases. This study aims to evaluate the effects of strength training on glycemic parameters after a single exercise session in adults with T1DM.
Keywords: Diabetes mellitus; training; blood pressure